2016
DOI: 10.1155/2016/7676512
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Spatial Memory and Synaptic Plasticity Impairment Is Preventable by Captopril

Abstract: Introduction. Renin-angiotensin system has a role in inflammation and also is involved in many brain functions such as learning, memory, and emotion. Neuroimmune factors have been proposed as the contributors to the pathogenesis of memory impairments. In the present study, the effect of captopril on spatial memory and synaptic plasticity impairments induced by lipopolysaccharide (LPS) was investigated. Methods. The rats were divided and treated into control (saline), LPS (1 mg/kg), LPS-captopril (LPS-Capto; 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 42 publications
(58 reference statements)
2
22
0
Order By: Relevance
“…The short-term spatial memory tested in the Y-maze and long-term object recognition memory tested in NORT are hippocampus-dependent memory types (Cohen et al, 2013; Albani et al, 2014; Pioli et al, 2014). Inflammation in the hippocampus is reported to have impaired these types of memory, and the suppression of inflammation subsequently improved these memory impairments (Miwa et al, 2011; Abareshi et al, 2016). Evidence from these reports together with the findings in our present study suggest that dietary IAA is capable of suppressing microglial inflammatory responses in aged mice, which might be associated with the prevention of the decline in hippocampal memory associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…The short-term spatial memory tested in the Y-maze and long-term object recognition memory tested in NORT are hippocampus-dependent memory types (Cohen et al, 2013; Albani et al, 2014; Pioli et al, 2014). Inflammation in the hippocampus is reported to have impaired these types of memory, and the suppression of inflammation subsequently improved these memory impairments (Miwa et al, 2011; Abareshi et al, 2016). Evidence from these reports together with the findings in our present study suggest that dietary IAA is capable of suppressing microglial inflammatory responses in aged mice, which might be associated with the prevention of the decline in hippocampal memory associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting neurocognitive dysfunction has much the same origins as microglial activation induced by PICs but there is some evidence to suggest that the adverse effects on adult neurogenesis, memory deposition and recall, synaptic plasticity and long-term potentiation following elevated systemic LPS is primarily mediated by elevated IL-1β in the hippocampus (Abareshi et al 2016; Li et al 2017; Nolan et al 2005). …”
Section: Consequences Of Chronic Systemic Iandonsmentioning
confidence: 99%
“…This view has been encompassed in the "fetal origin of adult disease" hypothesis (Benarroch, 2013). Studies have indicated that exposure to inflammation in the embryonic period (Qin et al, 2007;Abareshi et al, 2016) or to stress in adolescence (Speisman et al, 2013;Shields et al, 2017) may be involved in the occurrence of the age-associated learning and memory impairments.…”
Section: Introductionmentioning
confidence: 99%